Production, Optimization And Partial Purification Of L-Asparaginase From Endophytic Fungus Aspergillus Sp., Isolated From Cassia Fistula (Applied Biological Research, 2020)
Endophytes are relatively less studied microbes which in future may serve as  potential sources of novelsecondarymetabolites for use in medical,  agricultural and pharmaceutical industries. In present study six fungal  endophytes were isolated from the leaves, stem and fruit of Cassia fistula and  screened for asparaginase production on modified Czapek Dox agar  supplemented with L-asparagine as a substrate and phenol red as indicator.  L-asparaginase production by Aspergillus sp. using variable carbon and nitrogen sources, temperature and pH revealed maximum asparaginase production with xylose as carbon source and ammonium nitrate as nitrogen sources at pH 6.0 with incubation temperature of 30˚C. The disc size optimization for enzyme revealed maximum activity with 10 mm size disc (0.22 IU mg-1enzyme activity). The endophyte studied showed maximumactivity under stationary condition (2.7 IU mg-1) than under shaking condition. Various purification steps included salt precipitation, dialysis, followed by separation on Sephadex G-100 gel filtration. The partially purified enzyme showed the activity of 4.9 IU mg-1. It may be concluded that the isolated Aspergillus sp. may serve as a vital source of L-asparaginase for future use.
Keywords: Cancer; L-asparaginase; Cassia fistula; leukemia; lymphoma